Peritoneal and upper genital tract tuberculosis - Alexandra Wagner; Ruža Arsenić; Matthias David; Jalid Sehouli; Domagoj Vidosavljević; Irena Rohr (Medicinski glasnik, 2019)
Aim: To present diagnostic and therapeutic possibilities for genital and peritoneal tuberculosis, mimicking to other pathological conditions, mainly, ovarian cancer. Methods: Transabdominal and transvaginal ultrasound, computerized tomography, Ca125 and HE 4, ROMA-index (Risk of Ovarian Maligancy Algorithm index) and diagnostic laparoscopy were performed in order to diagnose genital tuberculosis in a female patient. Results: A 23-year-old woman from Morocco presented with intermitting abdominal pain, unintentional weight loss and primary infertility. There was no positive family history for breast or ovarian cancer and no history of previous tuberculosis (TB). Elevated CA-125 level, HE 4 normal, ROMA-Index of 13.2 % suggested high risk for epithelial ovarian cancer (EOC). Ultrasound revealed free fluid, dilated fallopian tubes and a cystic mass near the right ovary. Suspecting fallopian tube or ovarian cancer, we performed exploratory laparoscopy, revealing adhesions, multiple miliary nodes and dilated fallopian tubes. Histological investigation revealed granulomatous abscessing salpingitis with suspicion of genital TB, so antituberculous therapy was administered with success. Conclusion: Female genital tuberculosis is very rare but important in differential diagnosis and should be kept in mind regarding suspected fallopian tube or ovarian carcinoma to prevent women from extensive surgery. An algorithm for possible differentiation between peritoneal/female genital TB and EOC may be helpful in clinical setting.
Keywords: ovaries; peritoneum; tuberculosis